Impact of Corporate Governance Practices on Firm Performance in Malaysia - Shir Ying, Tan; Rayappan, Patricia (International Journal of Psychosocial Rehabilitation, 2020)
Maintaining good corporate governance practices are significant to prevent firm failures. The corporate governance dilemma has raised concerns in both developed and developing countries. This paper examined the impact of corporate governance practices on firm performance in Malaysia. There are four main corporate governance practices to be tested in this study, which composed of boards independence, size of board, board diversity and board remunerations.